The impact of extended electrodiagnostic studies in Ulnar Neuropathy at the elbow - Todnem, Kari (BioMed Central, 2009)
BACKGROUND: This study aimed to explore the value of extended motor nerve conduction studies in patients with ulnar nerve entrapment at the elbow (UNE) in order to find the most sensitive and least time-consuming method. We wanted to evaluate the utility of examining both the sensory branch from the fifth finger and the dorsal branch of the ulnar nerve. Further we intended to study the clinical symptoms and findings, and a possible correlation between the neurophysiological findings and pain. METHODS: The study was prospective, and 127 UNE patients who were selected consecutively from the list of patients, had a clinical and electrodiagnostic examination. Data from the most symptomatic arm were analysed and compared to the department's reference limits. Student's t - test, chi-square tests and multiple regression models were used. Two-side p-values < 0.05 were considered as significant. RESULTS: Ulnar paresthesias (96%) were more common than pain (60%). Reduced ulnar sensitivity (86%) and muscle strength (48%) were the most common clinical findings. Adding a third stimulation site in the elbow mid-sulcus for motor conduction velocity (MCV) to abductor digiti minimi (ADM) increased the electrodiagnostic sensitivity from 80% to 96%. Additional recording of ulnar MCV to the first dorsal interosseus muscle (FDI) increased the sensitivity from 96% to 98%. The ulnar fifth finger and dorsal branch sensory studies were abnormal in 39% and 30% of patients, respectively. Abnormal electromyography in FDI was found in 49% of the patients. Patients with and without pain had generally similar conduction velocity parameter means. CONCLUSION: We recommend three stimulation sites at the elbow for MCV to ADM. Recording from FDI is not routinely indicated. Sensory studies and electromyography do not contribute much to the sensitivity of the electrodiagnostic evaluation, but they are useful to document axonal degeneration. Most conduction parameters are unrelated to the presence of pain.